The science of gun policy : a critical synthesis of research evidence on the effects of gun policies in the United States (RAND, 2018)
The RAND Corporation's Gun Policy in America initiative is a unique attempt to systematically and transparently assess available scientific evidence on the real effects of firearm laws and policies. Good gun policies require consideration of many factors, including the law and constitutional rights, the interests of various stakeholder groups, and information about the likely effects of different laws or policies on a range of outcomes. This report seeks to provide the third -- objective information about what the scientific literature examining gun policy can tell us about the likely effects of laws. The study synthesizes the available scientific data on the effects of various firearm policies on firearm deaths, violent crime, the gun industry, participation in hunting and sport shooting, and other outcomes. -- Provided by publisher